Plasma Glucose Lowering Activity of Palmatine and its Effect on Liver, Kidney and Antioxidant Enzymes Parameters in STZ Induced Diabetic Rat Model - Ogechi Ekeuku, Sophia; Nwabueze Okechukwu, Patrick; Akyirem Akowoah, Gabriel; Swee Sen, Teo; Namatama Siyumbwa, Stepfanie; Ruth Anisah Froemming, Gabriele (Current Bioactive Compounds, 2015)
Diabetic mellitus is a metabolic disease primarily defined by the level of hyperglycemia that gives rise to complications such as retinopathy, nephropathy, and neuropathy. Reactive oxygen species (ROS) generation and impaired antioxidant defense systems have been implicated in the development of diabetes mellitus. Palmatine is a protoberberine alkaloid has shown potential for the treatment of hypertension, inflammation, and liver-related diseases. Our study aimed at evaluating the blood plasma glucose lowering, in vivo antioxidant, liver and profile activity of palmatine in an STZ-induced diabetic rat model. Streptozotocin (STZ) was administered by intraperitoneal injection to induce diabetes in Sprague dawley rats. A week later rats with plasma glucose level of 11mmol/L or 200mg/dL and above were orally administered with palmatine (2mg/kg) for 90 days. The blood glucose level and body weight of the rats were measured weekly. After 90 days of treatment, the rat blood was withdrawn via cardiac puncture and liver and pancreas were harvested after they were sacrificed by cervical dislocation. Palmatine significantly decreased the blood plasma glucose and lipid peroxidation compared to the positive control Tolbutamide. While the activity of the antioxidant defense system and blood parameters were normalised. Palmatine significantly (P<0.0001) reduced the blood plasma glucose level, increased the weight of the rats in palmatine treated group, plasma glucose parameters and in vivo antioxidant activity In conclusion plamatine improved blood glucose levels and reduced the oxidative stress. Therefore it may be considered in the treatment of diabetes.
Keywords: histology